الحماية الجنائية للطفل من الجرائم الجنسية على ضوء قانون العقوبات والاجتهاد القضائي الجزائري - حفناوي, مدلل; شنوف, بدر الدين (University of Eloued جامعة الوادي, 2020)
يهدف هذا المقال إلى تحليل النصوص القانونية الواردة في قانون العقوبات الجزائري التي تهدف إلى حماية الطفل من الجرائم الجنسية المرتكبة ضده، والتي تعتبر الدعامة الأساسية لحمايته جنائيا كما يهدف أيضا إلى إبراز دور الإجتهاد القضائي في ذلك، من خلال تحليل قرارات المحكمة العليا باعتبارها السلطة العليا المنوط بها مراجعة الأحكام الصادرة عن القضاء في هذا المجال، وعليه جاءت هذه الدراسة لتبين مدى دور التشريع، ومن بعده القضاء الجنائي في الحد من الانتهاكات الجنسية التي يكون الطفل القاصر فيها دائما هو الضحية. This paper aims to analyze the legal texts contained in the Algerian Penal Code that purpose to protect the child from sexual crimes committed against him, which are the mainstay of his criminal protection. Besides, it aims to highlight the role of judicial jurisprudence that related to this rules through scrutinizing the decisions of the Supreme Court as the Supreme Authority Entrusted with reviewing judgments issued by the judiciary in this field. Consequently, this study undertaking to show the extent of the legislation's role and then the criminal judiciary in limiting sexual violations in which the minor child is always the victim.
مجلد 11، عدد3
Keywords: الحماية الجنائية ؛ الطفل؛ الجرائم الجنسية؛ قانون العقوبات؛ المحكمة العليا; Criminal protection; Child; Sexual crimes; Penal Code; Supreme Court.